Comparative evaluation of the glucose level in dogs and cats obtained by portable glucometer and colorimetric automated method (Research, Society and Development, 2020)
Glucose is an essential carbohydrate for the good functioning of the organism and in normal conditions it is able to maintain the glucose in adequate levels. The glucose can be measured by the portable glucometer or by the laboratory method, which is considered the standard methodology, but with disadvantages such as cost and the necessary amount of blood. The portable glucometer shows itself to be an applicable option because it is less expensive and faster. This prospective clinical study aimed to compare and evaluate the efficiency between the OneTouch UltraMini® portable monitor and the automated colorimetric method for measuring the blood glucose concentration of 48 dogs and 20 cats.  The results obtained from the mean of the portable monitor and laboratory method were 87.54 mg/dL and 94.47 mg/dL for dogs, and 85.95 mg/dL and 100 mg/dL for cats, respectively. It could be concluded that the comparison between the methods showed that the portable meter represents an excellent option for measuring blood glucose in dogs and cats.